Histopathological Findings in Sudden Cardiac Death: 5-years Autopsy Experience in a Tertiary Hospital in Bandung, Indonesia - Gian Nugraha; Nita Novita; Hermin Aminah Usman (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Sudden death (SD) is a sudden and unexpected death with an unknown cause. However, it has been assummed that the most common causes of sudden deaths are cardiovascular or non-cardiovascular causes such as gastrointestinal disease, respiratory disease, genitourinary disease, epilepsy, and trauma. This study aimed to portray histopathological findings and causes of sudden cardiac death (SCD) cases based on 5 year autopsy experience in a tertiary hospital in Bandung, Indonesia. Methods: This study was a descriptive cross-sectional study exploring causes of SCD from 2015 to 2019 at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. All medical records with SCD and histopathology findings were retrieved from September to December 2020. Only cases with histopathological examination results were included.Results: SCD was found in 7 of 16 patients with sudden death. Coronary atherosclerosis was the most common (n=4), followed by myocardial infarction (n=2) and ruptured aortic aneurysm (n=1). Myocarditis and calcific aortic valve diseases were not found.Conclusions: In this study, the most common cause of SCD is coronary atherosclerosis, which is identified mainly in older and male patients.